IS BISPHENOL A (BPA) A PUBLIC HEALTH CONCERN? A CROSS-SECTIONAL STUDY OF PUBLIC KNOWLEDGE, ATTITUDE AND RISK PERCEPTION IN SOUTHWESTERN PART OF NIGERIA - Omoyajowo, Koleayo; Agbaogun, Babatunde; Ogunyebi, Amos; Kanaan, Manal; Omoyajowo, Busayo; Makengo, Benjamin Mwadi; Alayemi, Ayodele; Omoyajowo, Kolawole; Alao, Rebecca (FUDMA Journal of Sciences, 2024)
Bisphenol A (BPA) is a chemical produced in large quantities for use primarily in the production of polycarbonate plastics and epoxy resins. Exposure to BPA is a public health concern because studies since the last decade have consistently linked BPA with several physiological disorders such as cardiovascular diseases, neurological, obesity, and some forms of cancers. Hence, this study assessed the level of BPA knowledge and awareness among randomly selected individuals in the Southwestern part of Nigeria. This study employed a mixed-methods approach, utilizing a survey specifically designed to collect data for the research. Different statistical methods were utilized including descriptive and inferential to analyze the data and to assess exploratory variables such as public knowledge, attitude, and risk perception. Findings revealed that though 96.2 % knew chemicals in plastics could cause adverse health effects, the level of knowledge on BPA and its attendant health risks among the sample population was abysmally low (only 35% knew this subject). However, most of our respondents interestingly expressed great attitude in terms of willingness to share information learned about BPA to others in the community. Based on the findings of this study, a massive awareness campaign about BPA and associated health risks would be required through effective scientific communication to improve public health outcomes.